Bovine congenital babesiosis - Henker, Luan Cleber; Lorenzett, Marina Paula; Pavarini, Saulo Petinatti (Brazilian Journal of Veterinary Pathology, 2021)
A crossbred, stillborn bovine fetus, with nine months of gestation, was submitted for postmortem examination. The dam that aborted was a 2-year-old heifer that did not have any additional clinical signs. The owner observed several late-term abortions and stillbirths in this farm during the referred calving season.